OOCYTE MORPHOMETRY IN BITCHES FROM VARIOUS AGES AND REPRODUCTIVE MATURITY STATUS - Sheren, Sheren; Susari, Ni Nyoman Werdi; Trilaksana, I Gusti Ngurah Bagus (Buletin Veteriner Udayana, 2023)
Dog is one of the animals that has been human’s pet for thousands of years. The aim of this study was to find the morphometry of canine oocyte from various age and reproductive maturity status. In this study, 22 pairs of ovarium samples were collected and stored with Phosphate Buffer Saline (PBS) as transport media. Oocytes were collected using the method of slashing, where multiple slashes were made on the cortex of ovaries and then flushed with NaCl. Petri dish containing NaCl were then observed under the microscope to find the oocyte. Oocyte diameter was obtained by averaging two measurements made perpendicular to each other. If oocytes are obscured by cumulus cells, measurement was taken diagonally. Measurements taken were diameter of oocyte (including zona pellucida) and diameter of ooplasma. Based on statistical analysis of this study using one-way ANOVA, showed oocyte and ooplasma diameters from groups of prepubertal, <1 year old post-pubertal (juvenile), 1-4 years old (mature), and >4 years old (old) are almost indistinguishable. Oocytes from mature dogs had the largest diameter (oocyte = 108,0±27,8µm and ooplasma = 85,7±19,5µm) and was sigfinicantly larger than oocytes from prepubertal dogs (oocyte = 102,5±29,4µm and ooplasma = 84,8±25,4µm). Juvenile dogs had the smallest diameter (oocyte = 94,1±28,9µm and ooplasma = 78,8±25, µm), followed by old dogs (oocyte = 98,5±38,7µm and ooplasma 83,01±35,1µm). Further investigations of oocyte morphometry are needed while focusing more on follicle size, estrus cycle, and oocyte quality.